TLR-2 and MyD88-Dependent Activation of MAPK and STAT Proteins Regulates Proinflammatory Cytokine Response and Immunity to Experimental Trypanosoma congolense Infection - Kuriakose, Shiby (Front Immunol, 2019)
It is known that Trypanosoma congolense infection in mice is associated with increased production of proinflammatory cytokines by macrophages and monocytes. However, the intracellular signaling pathways leading to the production of these cytokines still remain unknown. In this paper, we have investigated the innate receptors and intracellular signaling pathways that are associated with T. congolense-induced proinflammatory cytokine production in macrophages. We show that the production of IL-6, IL-12, and TNF-α by macrophages in vitro and in vivo following interaction with T. congolense is dependent on phosphorylation of mitogen-activated protein kinase (MAPK) including ERK, p38, JNK, and signal transducer and activation of transcription (STAT) proteins. Specific inhibition of MAPKs and STATs signaling pathways significantly inhibited T. congolense-induced production of proinflammatory cytokines in macrophages. We further show that T. congolense-induced proinflammatory cytokine production in macrophages is mediated via Toll-like receptor 2 (TLR2) and involves the adaptor molecule, MyD88. Deficiency of MyD88 and TLR2 leads to impaired cytokine production by macrophages in vitro and acute death of T. congolense-infected relatively resistant mice. Collectively, our results provide insight into T. congolense-induced activation of the immune system that leads to the production of proinflammatory cytokines and resistance to the infection.